Interfaith and Cultural Community Meeting in Weaving National Identity Based on the Huma Betang Philosophy in Palangka Raya - Pattiasina, Sharon Michelle O. (Jurnal Sosiologi Agama, 2024)
Palangka Raya is characterized by ethnic, cultural, and religious diversity. It shows that the Dayak people, as indigenous people, have lived alongside the immigrants. Huma Betang’s philosophy significantly affects society across religions and cultures. This research aims to analyze the implementation of the Huma Betang philosophy in cross-religious and cultural community encounters in knitting national identity in Palangka Raya. This research uses a qualitative method with a sociology of religion approach. In this case, the data collection techniques are observation, interviews, and literature study. The results of the research found that the existence of the Palangka Raya community in the socio-cultural and religious space is based on the Huma Betang philosophy and the motto Bumi Tambun Bungai Bumi Pancasila. These two things are not only implemented for fellow Dayak tribes but also for people with different backgrounds who are categorized as immigrants in Palangka Raya. It is strengthened by the community’s appreciation of humanitarian actions. In this way, the experience of living together in a space across religions and cultures becomes a national spirit based on humanitarian action.